Action potentials and subthreshold potentials of dorsal horn neurons in a rat model of myositis: a study employing intracellular recordings in vivo - Hoheisel, Ulrich; Chacur, Marucia; Treede, Rolf-Detlef; Mense, Siegfried (Journal of neurophysiology, 2019)
Intracellular in vivo recordings from rat dorsal horn neurons were made to study the contribution of microglia to the central sensitization of spinal synapses induced by a chronic muscle inflammation. To block microglia activation, minocycline was continuously administered intrathecally during development of the inflammation. The aim was to test whether an inflammation-induced sensitization of dorsal horn neurons is mediated by changes in synaptic strength or other synaptic changes and how activated microglia influence these processes. Intracellular recordings were used to measure subthreshold excitatory postsynaptic potentials (EPSPs) and suprathreshold action potentials (APs). The muscle inflammation significantly increased the proportion of dorsal horn neurons responding with APs or EPSPs to electrical stimulation of the muscle nerve from 27 to 56% (P < 0.01) and to noxious muscle stimulation (3 vs. 44%, P < 0.01). Neurons showing spontaneous ongoing AP or EPSP activity increased from 28 to 74% (P < 0.01). Generally, the increases in suprathreshold AP responses did not occur at the expense of subthreshold EPSPs, because EPSP-only responses also increased. Intrathecal minocycline prevented the inflammation-induced increase in responsiveness to electrical (24%, P < 0.02) and mechanical stimulation (14%, P < 0.02); the effect was stronger on suprathreshold APs than on subthreshold EPSPs. The increase in ongoing activity was only partly suppressed. These data suggest that the myositis-induced hypersensitivity of the dorsal horn neurons to peripheral input and its prevention by intrathecal minocycline treatment were due to both an increase in the number of active synapses and an increased synaptic strength.NEW & NOTEWORTHY During a chronic muscle inflammation (myositis), activated microglia controls both the increase in the number of active synapses and the increase in synaptic strength.